Enhancing stability and voltage quality in remote DC microgrid systems through adaptive droop control approach - Lam, Hong Phuc; Nguyen, Hung Duc; Pham, Minh Duc (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
To ensure the stable and accurate operation of "rural areas”, a reliable power source is necessary, and voltage issues must be carefully considered in power system design to ensure patient safety. Remote DC microgrids provide a viable option for transferring energy across power sources while assuring stability and high efficiency. In this paper, an adaptive droop control approach is developed and compared to the standard droop control method. The suggested technique recommends a dynamic modification of droop coefficients intending to effectively limit the buildup of mistakes in current sharing and departures from the preset voltage setpoints. Through the implementation of the adaptive droop control method, the remote DC microgrid not only enhances current balancing performance but also contributes to a substantial improvement in voltage stability, thereby increasing the overall operational efficiency of the system. Simulation and experimental results on a small-scale remote DC microgrid validate the proposed adaptive droop control approach, proving its effectiveness in the small-scale microgrid system.